Featuring Layers of Abstraction as a Modeling Resource in an Educational Game-Based Learning Platform - Silva Junior, Braz Araujo da; Silva, Júlia Veiga da; Cavalheiro, Simone André da Costa; Foss, Luciana (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2023: Anais do XXXIV Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/sbie.2023.235276, 2023)
This paper presents a feature supporting the modeling, management and visualization of layers of abstraction in an educational game engine. Computer science education has conquered significant recognition supported by the concept of Computational Thinking, an essential skill set in a world where computing is pervasive. One of its pillars, abstraction, has many facets on its own, and some of them still struggle to find support of educational tools. Attempting to fill this gap, this work proposes a resource that allows grouping elements while modeling games. Abstract hierarchical graph grammars are used as theoretical foundation and practical examples of how it fosters abstraction are given. The processes found to be possible to grasp with it are generalization, refining, modularization, nesting and navigation through layers of abstraction.